A comparison between root canal transportation of Waveone Gold and Protaper Next files, using micro-computed tomography - Gajoum, Abdulrzag (My University, 2018)
Purpose: Transportation is one of the main preparation errors in root canal treatment and has been used as a tool to evaluate the shaping ability of filing systems. This study compared the root canal transportation and centering ability produced between WaveOne Gold (WOG) and ProTaper Next (PTN) files in curved permanent teeth using Micro-computed tomography (μCT). Methods: Twenty-four teeth with curved roots were divided randomly into two groups. Pre-instrumentation μCTs were taken for all the teeth. One group was filed using WOG files, and the other group using PTN files. Following post-instrumentation: cross-sectional images were taken at 3, 5 and 7mm from the radiographic apex of the pre-and the post-instrumentation images of each tooth. The dentine thickness of the pre-and the post-instrumentation cross sections was measured at eight different points by two dentists using μCT software. The data was analysed using one-way ANOVA, at a 5% significance level. Results: The WOG file exhibited significantly less root canal transportation compared to the PTN file (p=0.001). However, the findings of apical root canal transportation was within an acceptable range in both groups, between 0.0229 and 0.0621mm. Use of the WOG file showed a significantly (p< 0.001) higher mean centering ratio of 0.4286 when compared to PTN which showed a centering ability ratio of 0.2448. Conclusions: Within the limitations of this study, the WOG files showed superior ability to shape root canals with fewer errors as well as the ability to keep the root canal centred when compared with PTN files.
A research report submitted to the Faculty of Health Sciences, University of the Witwatersrand, in partial fulfilment of the requirements for the degree of Master of Science in Dentistry. School of Oral Health Sciences, Faculty of Health Sciences, University of the Witwatersrand, Johannesburg, South Africa 2017.
Keywords: Root Canal Transportation; Root Canal Therapy